Perspectives of patients with early psychosis on the use of an app in acceptance and commitment therapy: a qualitative study - Bouws, Jara; Uyttebroek, Lotte; Beames, Joanne R.; de Koning, Mariken; Schirmbeck, Frederike; Henrard, An; Reininghaus, Ulrich; de Haan, Lieuwe; Myin-Germeys, Inez (Early intervention in psychiatry, 2025)
Introduction Individuals with early psychosis received Acceptance and Commitment Therapy in daily life (ACT-DL), consisting of 8 face-to-face sessions and use of a mobile app at home, as part of a randomised controlled trial (INTERACT). Those receiving ACT-DL showed improvement in negative symptoms and global functioning compared to the control condition. The current study qualitatively explores patients' perspectives on the ACT-DL app and perceived areas for improvement. Methods The ACT-DL app prompted individuals randomly multiple times a day between therapy sessions to complete questionnaires (Ecological Momentary Assessments, EMA) and ACT metaphors or exercises (Ecological Momentary Interventions, EMI). User experiences with the ACT-DL app were explored in 17 semi-structured interviews within 6 months after the intervention and analysed using template thematic analysis. Results Three themes were formed: 1. App functionalities and usability; consisting mainly of perceived practical obstacles. 2. Additional value of the app; on how the EMAs raised levels of awareness for feelings, thoughts, and behaviour, and the positive evaluation of the ACT exercises in the EMI part of the app. 3. Improving applicability and effect of the ACT-DL app; with practical feedback from participants. Conclusions Individuals with early psychosis were generally positive about the effects of the ACT-DL app, attributing benefits to increased awareness via EMAs and to the ACT exercises. However, they experienced difficulties using the app during work and social activities. Participants provided valuable suggestions to improve the app's effectiveness and applicability.